2007
DOI: 10.1002/ijc.23119
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CCR5 receptors on Reed–Sternberg cells and Hodgkin lymphoma cell lines: Involvement of CCL5/Rantes in tumor cell growth and microenvironmental interactions

Abstract: The expression of CCL5/Rantes by Hodgkin (H) and Reed-Sternberg (RS) cells has been recently documented. In the present study we demonstrated that the CCL5 receptor (CCR5) is constitutively expressed by Hodgkin Lymphoma (HL)-derived cell lines (i.e. L-428, KM-H2, L-1236 and L-540) as shown by immunohistochemistry, flow cytometry and western blotting and also detected by immunohistochemistry on primary H-RS cells from lymph node tissues. sCD40L never significantly affected CCR5 expression, whereas a short expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
123
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 140 publications
(134 citation statements)
references
References 42 publications
6
123
0
2
Order By: Relevance
“…As we confirm here, RS cell proliferation alone is insufficient for expansion or maintenance of the HRS cell clone. However, considering the longevity of RS cells, as shown here, as well as the important role of the microenvironment in HL (16,37,38), one may speculate that RS cells support tumor clone survival and expansion by producing cytokines and chemokines and promoting cellular interactions with other immune cells (39)(40)(41)(42), shaping the HL microenvironment in a way that supports the proliferating Hodgkin cells (43)(44)(45)(46). Based on this idea, understanding the mechanisms involved in fusion-based RS cell formation might lead to new therapeutic interventions making use of this process.…”
Section: Discussionmentioning
confidence: 92%
“…As we confirm here, RS cell proliferation alone is insufficient for expansion or maintenance of the HRS cell clone. However, considering the longevity of RS cells, as shown here, as well as the important role of the microenvironment in HL (16,37,38), one may speculate that RS cells support tumor clone survival and expansion by producing cytokines and chemokines and promoting cellular interactions with other immune cells (39)(40)(41)(42), shaping the HL microenvironment in a way that supports the proliferating Hodgkin cells (43)(44)(45)(46). Based on this idea, understanding the mechanisms involved in fusion-based RS cell formation might lead to new therapeutic interventions making use of this process.…”
Section: Discussionmentioning
confidence: 92%
“…HRS cells express the chemokine receptor CCR5 and abundantly secrete its cognate ligand CLL5. 25 In addition, signaling through the CCR5/CCL5 system regulates HRS cell growth. 25 Furthermore, interleukin 13 (IL-13) and its receptor have been shown to be frequently expressed in cultured and primary HRS cells.…”
Section: Discussionmentioning
confidence: 99%
“…25 In addition, signaling through the CCR5/CCL5 system regulates HRS cell growth. 25 Furthermore, interleukin 13 (IL-13) and its receptor have been shown to be frequently expressed in cultured and primary HRS cells. 27 Treatment of cultured HRS cells with IL-13-neutralizing antibodies resulted in a dosedependent proliferation arrest, indicating IL-13 involvement in HRS cell growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Buri et al found that CCL5 was only expressed in the infiltrated non-neoplastic leukocytes of CHL but not in HRS cells (6). However, subsequent studies demonstrated the expression of CCL5 in HRS cells and its potential role in the recruitment of inflammatory cells into lymphoma tissue (7,8). Emmerich et al found that NF-кB transcription factor iкBα is overexpressed in RS cells (9).…”
Section: Introductionmentioning
confidence: 99%